Conceptualization of physical exercise and keeping fit by child wheelchair users and their parents. (22nd December 2016) - Noyes, Jane; Spencer, Llinos Haf; Bray, Nathan; Kubis, Hans‐Peter; Hastings, Richard P.; Jackson, Matthew; O'Brien, Thomas D.
Abstract: Aim: To gain a better understanding of how children aged 6–18 years who use wheelchairs and their families conceptualized physical exercise and keeping fit. Background: Disabled children with reduced mobility are commonly overweight and unfit. Nurse‐led health screening programmes in schools commonly exclude disabled children if they cannot use standard weighing scales or stand against height measuring sticks. Design: Qualitative interview study at two time points over 6 months with children who use wheelchairs and their families. Methods: Framework analysis using the theory of planned behaviour. Findings: Mainly physically active participants were recruited (24 children and 23 parents) 2013–2014. Despite engaging in high levels of physical exercise, children were assessed as fit but had elevated body fat and did not realize how fit they were or that they were slightly overweight and nor did their parents. Children enjoyed the social benefits of exercise. Unlike their parents, children confused the purpose and outcomes of physical exercise with therapy (e.g. physiotherapy) and incorrectly understood the effects of physical exercise on body function and strength, preventing stiffness, increasing stamina and reducing fatigue. A new model was developed to show children's misconceptions. Conclusions: Proactive parents can overcome barriers to enable their children to benefit from physical exercise. Professionals need to increase communication clarity to improve children's understanding of therapy compared with physical exercise outcomes. Inclusion of children who use wheelchairs in health education policy; routine health screening; physical education classes and teacher training requires improvement. Body composition measurement is recommended, for which nurses will need training.